Five-year visual results of intravitreal bevacizumab in refractory inflammatory ocular neovascularization - Mansour AM (Dove Medical Press, 2012)
Ahmad M Mansour,1,2 Friederike Mackensen,3 Padmamalini Mahendradas,4 Moncef Khairallah,5 Timothy YY Lai,6 Ziad Bashshur11Department of Ophthalmology, American University of Beirut, 2Rafic Hariri University Hospital, Beirut, Lebanon; 3Interdisciplinary Uveitis Center, University of Heidelberg, Heidelberg, Germany; 4Departments of Uveitis and Retina, Narayana Nethralaya, Bangalore, India; 5Department of Ophthalmology, Fattouma Bourguiba University Hospital, Monastir, Tunisia; 6Department of Ophthalmology and Visual Sciences, The Chinese University of Hong Kong, Hong Kong Eye Hospital, Kowloon, Hong KongPurpose: To assess the 5-year visual outcome of intravitreal bevacizumab in inflammatory ocular neovascularization.Methods: Retrospective, multicenter, consecutive case series of eight patients with inflammatory ocular neovascularization refractory to standard therapy who were treated with intravitreal bevacizumab and followed for 5 years after first injection. The outcome measures included improvement of best-corrected visual acuity expressed as logarithm of minimum angle of resolution.Results: Mean best-corrected visual acuity significantly improved from 0.58 at baseline (6/23 or 20/76; standard deviation = 0.32) to 0.20 at final assessment (6/10 or 20/32; standard deviation = 0.25) (n = 8; P = 0.02), a gain of 3.8 lines (median: three injections; eight eyes; eight patients). No ocular or systemic complications from intravitreal bevacizumab were noted.Conclusion: At 5 years, intravitreal bevacizumab sustained significant visual improvement in ocular neovascularization due to a variety of inflammatory ocular diseases without major complications after a median of three injections.Keywords: bevacizumab, choroidal neovascularization, punctate inner choroidopathy, toxoplasmosis, uveitis, Vogt–Koyanagi–Harada syndrome